Virtual leadership in intercontinental projects:a case study of the University of Santiago lms platform as an educational strategy - Samartinho, João (2020)
The implementation of a Learning Managment System (LMS) platform as a support to the course units of the degrees held at the University of Santiago (US), in Cape Verde, acts both as a project and an intercontinental challenge of educational and pedagogical exploration resources. At the same time it is an enhancer and bounding element of the education in an insular country formed by ten volcanic islands in the central region of the Atlantic Ocean, 570 kilometers from the western African coast. Due to the geographical dispersion of students, teachers and skilled technicians, distance teaching plays a major role in training, preparing an updating new professionals in different and diverse fields offered by the US. The implementation of an LMS platform project, which began in 2017 settles in a protocol of cooperation between two higher education institutions: the Polytechnic Institute of Santarém (IPSantarém) in Portugal and the University of Santiago located in the Santiago Island in Cape Verde. The project consists on development and personalization of a LMS platform to support teaching (degrees and masters) in e-Learning and blended-Learning models. The platform, a constant work in progress, is hosted on the IPSantarém server and the needed training for teachers and skilled technicians to use it correctly has been given through blended-Learning with face-to-face sessions in Cape Verde. Regarding the stages of conception, implementation, operationalization and development of the US LMS platform, the priority is bringing institutions closer by fostering bonds of cooperation, a growing and consistent trust based on effective dialogue supervised by technical teams that promote the training of teachers and IT staff by exploring e-Learning and blended-Learning environments present in the platform. This virtual leadership strategy is based on the 3Cs rule (Communication, Confidence and Coordination), Samartinho et al. (2014). It leads to a strategic synergy between two institutions where language and cultural bonds between the two peoples are clear. To enhance success the project adopts a model based on the role of the virtual leader (e-Leader) and his virtual work teams using specific IT tools. This model called ´´Model for the perception of the specific e-leadership skills and features in learning management systems environments´´ was suggested by Samartinho (2014) for global projects with characteristics and technical constrains identical to the ones here presented. For a better understanding of the project, a timeline of its development is presented (June 2017 - May 2019). Furthermore, a summary of the failures detected as well of the solutions found will be mentioned. The US LMS platform is an example of a successful project regarding implementation, development, training and spreading. It is on an assessment/development stage to ensure all the future training needs in the US degrees and for it to succeed the adopted model will be crucial. This project is also much benefited from the great commitment of all parts involved. The model used in this project is now expected to be adopted in future projects involving institutions from Africa, America and Asia where Portuguese is an official language.